Formulasi Permen Keras (Hard Candy) Kopi Defect Arabika Gayo - Irma Zarwinda; Nanda Nadia; Dwi Putri Rejeki (Journal of Pharmaceutical and Health Research, 2022)
Defect coffee is coffee that is defective or coffee that does not pass the quality control found in coffee beans at the sorting stage. This study aims to determine the quality characteristics of the Gayo Arabica defect coffee hard candy formulation with various concentrations of F1 (5%), F2 (10%), and F3 (15%) according to the requirements of SNI 3547.1:2008 concerning Hard Sugar Confectionery. The method used in this research is a laboratory experimental method. The manufacture of hard candy for Arabica Gayo coffee uses sugar as the main ingredient (sucrose), with other ingredients, namely glucose syrup, water, and extract of Gayo Arabica defect coffee. The time and place for the research is 22-24 April 2021, in the laboratory of the Academy of Pharmacy and Food Analysts (AKAFARMA) and the laboratory of Syiah Kuala University (UNSYIAH). Parameters of quality test carried out include organoleptic test, water content test, and ash content test. The results of the organoleptic test of the three hard candy formulations of Arabica Gayo coffee F1, F2 and F3 had normal color, taste and smell according to the requirements. The results of the research on the water content of the Gayo Arabica hard candy coffee are F1 (0.99%), F2 (0.79%), and F3 (0.66%), meeting the quality requirements for water content of not more than 3.5% . The results of testing the ash content of the three formulations are F1 (0.0531%), F2 (0.0907%), and F3 (0.2131%), according to the quality requirements of the ash content, which is not more than 2.0%. The quality characteristics of Gayo Arabica defect coffee hard candy with test parameters including organoleptic test, moisture content test, and ash content test of the three formulations met the quality requirements according to SNI 3547.1:2008 concerning Hard Sugar Confectionery.